2004
DOI: 10.1002/marc.200300181
|View full text |Cite
|
Sign up to set email alerts
|

Towards Green Routes for Polymer Synthesis: Polymerization of Cyclodextrin Host‐Guest Complexed Diethyl Fumarate and Copolymerization with Complexed Styrene in Homogenous Aqueous Solution

Abstract: Summary: The radical homo‐ and copolymerization of styrene (1) and diethyl fumarate (DEF, 2) in the presence of methylated β‐cyclodextrin (β‐CD) in water is described. It has been shown for the first time that homopolymerization of CD‐complexed DEF and its copolymerization with CD‐complexed styrene occur readily in aqueous solution. In the absence of CD, or in organic solvents, the homopolymerization of DEF is strongly retarded.image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Furthermore, the preparation and polymerization of equimolar cyclodextrin complexes of commercial standard monomers like styrene 1 and methyl methacrylate (MMA have been described. It was also shown that the precipitation polymerization of a cyclodextrin complex of a poorly water-soluble monomer like MMA can be described by kinetic equations similar to those for the classical polymerization in solution [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the preparation and polymerization of equimolar cyclodextrin complexes of commercial standard monomers like styrene 1 and methyl methacrylate (MMA have been described. It was also shown that the precipitation polymerization of a cyclodextrin complex of a poorly water-soluble monomer like MMA can be described by kinetic equations similar to those for the classical polymerization in solution [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The free-radical [5][6][7][8][9][10][11][12][13][14][15] and controlled 'living' [16] polymerizations of various CD-complexed vinyl derivatives and also some other types of monomers in water have recently been investigated. The synthesis of electrical conducting polymers from aqueous media via oxidative coupling have also been described, [17,18] and some kinetics of the homoand copolymerization of several kinds of CD-complexed monomers in aqueous medium have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] We have shown in the last decade that suitable monomers can easily be polymerized in water by a free radical mechanism after their encapsulation in methylated bcyclodextrin (RAMEB) without using any surfactants or cosolvents. [3][4][5][6][7][8][9][10][11][12][13][14] During the chain reaction, in many cases, the RAMEB molecules slip off stepwise while the waterinsoluble polymer chains precipitate.…”
Section: Introductionmentioning
confidence: 99%